The Influence of Viral Marketing and Consumptive Behavior on Purchase Decisions for Camille Beauty Skincare Products (Survey of Instagram Followers): marketing Management - Aditya Pandu Satryo; Liya Megawati (Fakultas Bisnis, 2022)
This study aims to determine, explain and analyze a phenomenon about the influence of viral marketing and consumptive behavior on purchasing decisions for Camille Beauty skincare products. This examination is an illustrative quantitative methodology. The examining method in this study utilized purposive testing with 384 respondents, in particular Instagram adherents @camille.beauty. In this review, the information utilized were Scale Reach Examination and Way Examination procedures with the assistance of the Technique for Succesive Span (MSI) , Microsoft Succeed 2016 and SPSS rendition 16. The outcomes showed that viral showcasing meaningfully affected buying choices with a level of 40.85 %, immoderate way of behaving significantly affects buying choices with a level of 21.30%. There is an impact of viral marketing and destructive conduct on buying choices that is equivalent to 62.1 % and the excess 37.9% is affected by different factors not analyzed in this review.